Population Structure of the Freshwater Crab Potamon algeriense (Bott, 1967) Inhabiting Oued Zegzel, (Northeast of Morocco). (20th December 2019) - Fadlaoui, Soufiane; Melhaoui, Mohammed
Abstract : This is the first study to determine the population structure of the freshwater crab Potamon algeriense in Oued Zegzel, a mountain stream in the northeast of Morocco. Monthly collections were carried out by hand, from October 2017 to September 2018. A total of 669 individuals, 378 males and 291 females, were captured, measured, marked, and released. Due to their extremely cryptic behavior during egg incubation, few ovigerous females were caught during the entire sampling period. The average size of males (28.98 ± 10.78 mm CW) is significantly larger than that of the females (28.62 ± 8.48 mm CW). Significant deviation from 1 : 1 sex ratio during the study period was recorded, and the size distribution of the sampled population presented an abnormal distribution where specimens over 31 and under 25 mm CW were often males, whereas females were represented more in the 26–30 mm CW range.